The Structure of the Brachial Plexus in Selected Representatives of the Caniformia Suborder - Arkadiusz Grzeczka; Maciej Zdun (Animals, 2022)
Like most structures, the brachial plexus is subject to species variation. Analysing this structure over a wide spectrum of species, we can obtain a complex view of the changes–in a given group of animals. The aim of this study was to describe the brachial plexus anatomy of species from two families of Caniformia. We analysed the brachial plexus structure of five species from two families of Caniformia: Canidae and Mustelidae. The cadavers were obtained from breeders and hunters. All were fixed by being kept in a 10% formaldehyde solution for two weeks. This study allows us to present the similarities as well as the differences between species and families. Our study reveals different trends in the course of the individual nerves and innervations of the thoracic limb. A species-specific feature is the extent of the brachial plexus, as each species has a specific number of ventral branches of the spinal nerves in the brachial plexus. However, a characteristic of the family Mustelidae is the course of the median nerve through the epicondylar foramen. Within the Canidae, two species are characterised by a very long branch for the coracobrachialis muscle. The general conclusion is that the brachial plexus of species belonging to the Caniformia is subject to variation within families and species, as well as individual variation while maintaining a general schematic for the group.